Efektifitas Aplikasi mHealth Terhadap Manajemen Nyeri Kanker Anak Usia Remaja: Literatur Review - Ayuni Rizka Utami; La Ode Abdul Rahman (Jurnal Keperawatan, 2020)
Pain is one of a problem in children suffering from cancer which affects to the quality of life of children, inhibits the recovery process, inhibits daily activities and result in long-term morbidity. Aim of this literature review is to identify the therapeutic effect of mHealth (Mobile Health) application for pain management of children suffering from cancer. This article is a literature review using several online databased such as: ClinicalKey, PubMed, Science Direct, ProQuest, EBSCO, Scopus, BioMed Central, and Google Scholar published from 2014-2019 using several of keywords. A selection of 10 full text articles was selected which was then analyzed. The analysis results of 10 articles about mHealth (Mobile Health) therapy in pain management in children suffering from cancer are effective, especially in the management of pain at home. Based on these results, the authors suggest to use mHealth (Mobile Health) therapy in children with cancer to support programmed therapy.